Self Control dan Phubbing pada Remaja - Lapalelo, Ingelsia; Purnomo, Jusuf Tjahjo (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Phubbing is ignoring people who have interpersonal relationships by checking cell phones. Self-control is the ability to regulate one's behavior, emotions, and thoughts in achieving long-term goals or values. This study aims to determine whether there is a correlation between self-control and phubbing behavior in male and female adolescents. This research used a quantitative approach with 337 participants, obtained using convenience sampling techniques. The data collection tools are the Self-control scale from Tangey, with 13 items, and the phubbing scale from Chotpitayasunondh and Douglas 2015, with 15 items. Data analysis uses Pearson's product-moment correlation technique. The results of the correlation test show r = 0.214 with a value of p = 0.000 (p<0.005), which means there is a reasonably strong relationship between self-control and phubbing and does not have a negative direction.